Edukasi tentang Internet agar Terhindar dari Penipuan Jual Beli Online di Desa Patimban Kecamatan Pusakanagara Kabupaten Subang - Endang Setiadi Permana; Deny Ernawan; Ade Suparman; Ahmad Burhanuddin (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this activity is to find out how much knowledge the local community in Patimban Village has regarding the internet to avoid fraud on online shopping sites or E-commerce. This Community Service Activity uses a field observation method (direct observation) by visiting people's homes through the distribution of information paper. The results of the activity concluded: first, online fraud is in principle the same as conventional fraud through the use of electronic systems (computers, internet, telecommunications devices) as a criminal act of fraud based on Law Number 11 of 2008 concerning Information and Electronic Transactions. Law enforcement officers often experience difficulties and obstacles in ensnaring perpetrators of fraud; and second, this criminal act of fraud can be charged with Article 378 of the Criminal Code as a criminal act of fraud or Article 28 paragraph (1) of the ITE Law concerning the regulation of the spread of false and misleading news that is detrimental to consumers. Or it can be charged based on both articles at once, namely, 378 of the Criminal Code in conjunction with Article 28 paragraph (1) in conjunction with Article 45 paragraph (1) of Law No. 11 of 2008 concerning fraud and/or ITE crimes.